Design of an IoT-based microclimate monitoring system for shallots in a greenhouse - Purbakawaca, Rady; Roidelindho, Kiki; Maulizar, Sonny Seftian; Hardyanto, Ichsan (Hexatech: Jurnal Ilmiah Teknik, 2025)
Shallots (Allium ascalonicum L.) are a high-value vegetable commodity that is strategically important for the Indonesian economy. However, shallot cultivation, particularly watering and fertilization, is still largely done manually, requiring human labor and simple equipment, making it less efficient and prone to errors in environmental monitoring. This study aims to design an Internet of Things (IoT)-based shallot microclimate monitoring system in greenhouses to improve the efficiency of automatic environmental monitoring. The method used includes the development of an ESP32 microcontroller-based system integrated with soil moisture sensors, temperature sensors, and air humidity sensors, as well as a GSM/GPRS wireless communication module for real-time data transmission. The system is also equipped with an alarm module to provide early warnings of unsuitable environmental conditions. Test results show that the system is able to operate stably and effectively in automatically monitoring microclimate changes in greenhouses. In conclusion, this IoT-based monitoring system can support more efficient shallot greenhouse management and reduce reliance on manual monitoring.